PARTICLE CREATION BY GRAVITATIONAL-FIELDS - Woodhouse, N (1976)
This paper presents a new and generally covariant approach to quantum field theory in curved space-time. Previously unknown expressions are obtained for particle creation amplitudes in oscillating gravitational fields. These expressions illuminate the physical origin of the particle creation. © 1976 The American Physical Society.